Development of new non-invasive tests for colorectal cancer screening: The relevance of information on adenoma detection - Haug, U.; Knudsen, A.; Lansdorp_Vogelaar, Iris; Kuntz, K. (John Wiley & Sons, Inc., 2015)
Researchers are actively pursuing the development of a new non-invasive test (NIT) for colorectal cancer (CRC) screening as an alternative to fecal occult blood tests (FOBTs). The majority of pilot studies focus on the detection of invasive CRC rather than precursor lesions (i.e., adenomas). We aimed to explore the relevance of adenoma detection for the viability of an NIT for CRC screening by considering a hypothetical test that does not detect adenomas beyond chance. We used the Simulation Model of Colorectal Cancer (SimCRC) to estimate the effectiveness of CRC screening and the lifetime costs (payers' perspective) for a cohort of US 50-years-old persons to whom CRC screening is offered from age 50–75. We compared annual screening with guaiac and immunochemical FOBTs (with sensitivities up to 70 and 24% for CRC and adenomas, respectively) to annual screening with a hypothetical NIT (sensitivity of 90% for CRC, no detection of adenomas beyond chance, specificity and cost similar to FOBTs). Screening with the NIT was not more effective, but was 29–44% more costly than screening with FOBTs. The findings were robust to varying the screening interval, the NIT's sensitivity for CRC, adherence rates favoring the NIT, and the NIT's unit cost. A comparative modelling approach using a model that assumes a shorter adenoma dwell time (MISCAN-COLON) confirmed the superiority of the immunochemical FOBT over an NIT with no ability to detect adenomas. Information on adenoma detection is crucial to determine whether a new NIT is a viable alternative to FOBTs for CRC screening. Current evidence thus lacks an important piece of information to identify marker candidates that hold real promise and deserve further (large-scale) evaluation.